Hedgehog/GLI signaling in tumor immunity - new therapeutic opportunities and clinical implications - Sandra Grund-Gröschke; Georg Stockmaier; Fritz Aberger (Cell Communication and Signaling, 2019)
Abstract Uncontrolled activation of the Hedgehog/Glioma-associated oncogene (HH/GLI) pathway is a potent oncogenic driver signal promoting numerous cancer hallmarks such as proliferation, survival, angiogenesis, metastasis and metabolic rewiring. Several HH pathway inhibitors have already been approved for medical therapy of advanced and metastatic basal cell carcinoma and acute myeloid leukemia with partially impressive therapeutic activity. However, de novo and acquired resistance as well as severe side effects and unexplained lack of therapeutic efficacy are major challenges that urgently call for improved treatment options with more durable responses. The recent breakthroughs in cancer immunotherapy have changed our current understanding of targeted therapy and opened up promising therapeutic opportunities including combinations of selective cancer pathway and immune checkpoint inhibitors. Although HH/GLI signaling has been intensely studied with respect to the classical hallmarks of cancer, its role in the modulation of the anti-tumoral immune response has only become evident in recent studies. These have uncovered HH/GLI regulated immunosuppressive mechanisms such as enhanced regulatory T-cell formation and production of immunosuppressive cytokines. In light of these exciting novel data on oncogenic HH/GLI signaling in immune cross-talk and modulation, we summarize and connect in this review the existing knowledge from different HH-related cancers and chronic inflammatory diseases. This is to provide a basis for the investigation and evaluation of novel treatments combining immunotherapeutic strategies with approved as well as next-generation HH/GLI inhibitors. Further, we also critically discuss recent studies demonstrating a possible negative impact of current HH/GLI pathway inhibitors on the anti-tumoral immune response, which may explain some of the disappointing results of several oncological trials with anti-HH drugs. Additional file 1Video abstract. (9500 kb)